Pengaruh bentuk gigi geligi terhadap terjadinya impaksi gigi molar ketiga rahang bawah - M. Hendra Chandha; Zia Nurul Zahbia (DiscoverSys Inc., 2007)
Teeth dimension is the factor influenced the incidence of toothimpaction. The most related factor with teeth dimension is teeth form.This study was aimed to determine the effect of teeth form on theincidence of lower third impaction. It was carried out on Buginese andTorajanese in South Sulawesi. The samples consist of 1! 5 Bugineseand 115 Torajanese, the age range from 20-25 years old with allnatural mandibular teeth including second molar. After impression ofboth upper and lower teeth was taken, each, tooth form wasdetermined by measurement with trubite tooth indicator. The frequencydistribution and coefficient corelation analysis test showed that therewas no significant difference between teeth form and incidence oflower third molar impaction in Buginese and Torajanese.